Potential plant-based new antiplasmodial agent used in Papua Island, Indonesia - Indradi, Raden Bayu; Muhaimin, Muhaimin; Barliana, Melisa Intan; Khatib, Alfi (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Resistance to antimalarial medicine remains a threat to the global effort for malaria eradication. The World Health Organization recently reported that artemisinin partial resistance, which was defined as delayed parasite clearance, was detected in Southeast Asia, particularly in the Greater Mekong subregion, and in Africa, particularly in Rwanda and Uganda. Therefore, the discovery of a potential new drug is important to overcome emerging drug resistance. Natural products have played an important role in drug development over the centuries, including the development of antimalarial drugs, with most of it influenced by traditional use. Recent research on traditional medicine used as an antimalarial treatment on Papua Island, Indonesia, reported that 72 plant species have been used as traditional medicine, with Alstonia scholaris, Carica papaya, Andrographis paniculata, and Physalis minima as the most frequently used medicinal plants. This review aimed to highlight the current research status of these plants for potential novel antiplasmodial development. In conclusion, A. paniculata has the highest potential to be developed as an antiplasmodial, and its extract and known bioactive isolate andrographolide posed strong activity both in vitro and in vivo. A. scholaris and C. papaya also have the potential to be further investigated as both have good potential for their antiplasmodial activities in vivo. However, P. minima is a less studied medicinal plant; nevertheless, it opens the opportunity to explore the potential of this plant.